2013
DOI: 10.4103/0019-5413.114915
|View full text |Cite
|
Sign up to set email alerts
|

Solid and hollow pedicle screws affect the electrical resistance: A potential source of error with stimulus-evoked electromyography

Abstract: Background:Although stimulus evoked electromyography (EMG) is commonly used to confirm the accuracy of pedicle screw placement. There are no studies to differentiate between solid screws and hollow screws to the electrical resistance of pedicle screws. We speculate that the electrical resistance of the solid and hollow pedicle screws may be different and then a potential source of error with stimulus-evoked EMG may happen.Materials and Methods:Resistance measurements were obtained from 12 pedicle screw varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Since this study was performed with direct current, and given the low capacitance of TiO 2 (<4.5 pF) [39], it is reasonable to expect that these capacitors will quickly become open circuits, leading all the current through the resistors. However, a series arrangement would require the sum of the TiO 2 and Ti-6Al-4V resistances, resulting in a larger model resistance and low conductivity, which is not in line with the results of experimental studies [7][8][9]40].…”
Section: Analytical Approachmentioning
confidence: 89%
“…Since this study was performed with direct current, and given the low capacitance of TiO 2 (<4.5 pF) [39], it is reasonable to expect that these capacitors will quickly become open circuits, leading all the current through the resistors. However, a series arrangement would require the sum of the TiO 2 and Ti-6Al-4V resistances, resulting in a larger model resistance and low conductivity, which is not in line with the results of experimental studies [7][8][9]40].…”
Section: Analytical Approachmentioning
confidence: 89%
“…Alternatively, alligator clips are commonly reported as the chosen coupling method in this type of study [12,18,19]. The jagged shape of the clip's teeth and the bracing force provided by the spring allow an apparent good grip to the screw' threads.…”
Section: Discussionmentioning
confidence: 99%
“…While some systematic reviews have identified the current thresholds associated to higher sensitivities of this IONM method [8][9][10], there is no complete explanation yet with respect to the high levels of heterogeneity and lack of agreement between studies on the best current stimulation threshold. This is a multifactorial issue caused by the multiple situations that may alter the normal nerve stimulation, which not only includes patient intrinsic aspects such as compressed nerve roots [11] but also extrinsic ones, such as the properties of the pedicle screw [12]. Although pedicle screws have been extensively characterized and analysed in terms of their biomechanical [13] and mechanical properties [14,15], the study of their electrical properties is still scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations